التغيرات الفصلية لأثر التلوث الجرثومي لمياه نهر الرميلة على المياه البحرية الشاطئية - العلي, بدر; عجيب, محمد (Latakia University Journal -Biological Sciences Series, 2018)
This study aimed to determine the abundance of heterotrophic bacteria in the water of the Alrmela River and coastal waters, study the changes of the faecal bacterial indicators distribution, and study of some hydrological properties and its effect on the indicators of faecal contamination. From March 2013 to February 2014, water samples were collected from seven stations with different environmental characteristics, distributed along the Alremela River near Jabla city and up to its estuary in the Mediterranean Sea. The results of the water temperature changes showed that were related to the moderate Mediterranean climate. Salinity values ranged from 0 to 39.33‰. The pH values did not decrease below 7 during the study period, and tend to rise towards the marine stations. The values of dissolved oxygen concentrations in water ranged between (2.51-7.59) mg / l. The results also showed that the total bacteria count values ranged between (81.5 - 666.6) × 104CFU / 100ml. The Total Coliform values ranged between (104 - 651.3) × 103CFU / 100ml. Faecal Coliform values ranged between (12-476.4) × 102CFU / 100ml, the values of Faecal Streptococcus count ranged between 2.6-118.6 × 102 CFU / 100ml. The water quality of the studied stations was based on the Total Coliform bacteria count, Faecal Coliforms and Faecal Streptococcus. The majority of the studied stations were considered to be contaminated and not recommended. The source of contamination was determined by the ratio value of Faecal Coliform bacteria to Faecal Streptococcus, It was from human origin in the majority of studied stations, while from animal or mixed origin during the winter. هدفت هذه الدراسة إلى تحديد غزارة الجراثيم غيرية التغذية في مياه نهر الرميلة والمياه الشاطئية، ودراسة تغيرات توزع المؤشرات الجرثومية البرازية وبعض الخواص الهيدرولوجية للمياه وتأثيرها في مؤشرات التلوث البرازي. جمعت عينات المياه شهرياً، من شهر آذار عام 2013 ولغاية شهر شباط عام 2014، من سبع محطات موزعة على مجرى نهر الرميلة بالقرب من مدينة جبلة وحتى مصبه في المياه البحرية للبحر المتوسط، تتمتع هذه المحطات بخصائص بيئية مختلفة. جرى تقييم جودة المياه في المحطات المدروسة، اعتماداً على تعداد جراثيم الكوليفورم الكلي، الكوليفورم البرازية والمكورات السبحية البرازية. أظهرت نتائج التغيرات الفصلية لدرجة حرارة المياه أنها كانت مرتبطة بالمناخ المتوسطي المعتدل. أما قيم الملوحة تراوحت بين 0-39.33 ‰، أما قيم الـ pH لمياه المحطات المدروسة لم تنخفض دون 7 خلال فترة الدراسة، ولوحظ أن هذه القيم تميل للارتفاع باتجاه المحطات البحرية. تراوحت قيم تراكيز الأوكسجين المنحل في المياه (2.51-7.59) mgł. أظهرت النتائج أيضاً أن قيم التعداد الكلي للجراثيم تراوحت بين (81.5-666.6) × 104CFU/100ml، وكانت أعلاها في فصل الخريف. أما قيم تعداد الكوليفورم الكلي تراوحت بين (104-651.3) × 103CFU/100ml. تراوحت قيم تعداد الكوليفورم البرازي بين (12-476.4) × 102CFU/100ml. كما تراوحت قيم تعداد المكورات السبحية البرازية بين (2.6-118.6) × 102CFU/100ml. لوحظ أن غالبية المحطات المدروسة تندرج تحت اعتبارها أنها ملوثة ولا ينصح بها للاستخدام البشري. أما تحديد مصدر التلوث إعتماداً على نسبة تعداد جراثيم الكوليفورم البرازي إلى جراثيم المكورات السبحية البرازية، فكان في معظم المحطات المدروسة ذو منشأ بشري، بينما كان ذو منشأ حيواني أو مختلط خلال فصل الشتاء.